How good can HDL Cholesterol be? Recent Evidence and way forward for Clinical Practice - Khan, Sikandar Hayat (Pakistan Armed Forces Medical Journal, 2023)
The science of “Lipidology” is flourishing in endless ways. The services included under the lipid testingdo not provide generalised risk assessment for possibleatherosclerotic cardiovascular disease (ASCVD) butprovide specialised services, including genomic andmolecular biomarkers for personalised care. The seminal discovery of lipoprotein fractions seems like a stepnext door in the much wider cosmos of metabolomicsand proteomics, where knowledge of lipoprotein subfractions as villains or saviours seems like the trailer ofthe Larger Amphitheatre. Low-density lipoproteins(LDL) though differently defined in the literature, werecategorised as “large buoyant LDL” (lbLDL) and“small dense LDL” (sdLDL).1 Over time, the knowledge base evolved to incorporate different fractionsamong lipoproteins based upon size and density withhigh-density lipoproteins (HDL) to incorporate nascentHDL, HDL2 and HDL3